Buxus holttumiana of Peninsular Malaysia and Thailand is a variety of B. cochinchinensis (Buxaceae) - Julius, Avelinah (Phytotaxa, 2014)
The Flora of Peninsular Malaysia project was initiated in 2005 (Kiew & Rafidah 2007, Saw & Chung 2007), and aims to document the entire flora of the region formerly known as Malaya or Malay Peninsula. As part of this project, the present author is revising the Buxaceae for the Flora, represented in Peninsular Malaysia by the single genus Buxus Linnaeus (1753: 983). The genus was last revised by Hatusima in 1942, and in his revision, Hatusima recognized three species in Peninsular Malaysia [viz. Buxus holttumiana Hatusima (1942: 270), B. malayana Ridley (1926: 475) and B. rupicola Ridley (1911: 166)]. All three taxa are confined to limestone forests at 20–450 m above sea level, and Hatusima (1942) considered all species as endemic to Peninsular Malaysia. In his revision, however, Hatusima described B. holttumiana  from a single collection gathered in 1938 from Kaki Bukit, Perlis (Kiah SFN 35239, see Figure 1A & B) and considered the thicker, shining leaves with fewer veins, the longer, erect (not strongly recurved and divaricating) styles as diagnostic characters for this species. Hatusima (1942), however, stated that he did not compare his new taxon with material of B. cochinchinensis Pierre ex Gagnepain (1921: 481), and his description of the latter was more or less a verbatim transcription of Gagnepain’s (Gagnepain 1921).